2021
DOI: 10.1093/jbcr/irab097
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Multiple-Drug Resistance Bacteria and Their Antimicrobial Resistance Patterns in Burn Infections from Southwest of Iran

Abstract: Background Burn infection continues to be a major issue of concern globally and causes more harm to developing countries. This study aimed to identify the aerobic bacteriological profiles and antimicrobial resistance patterns of burn infections in three hospitals in Abadan, southwest Iran. Methods The cultures of various clinical samples obtained from 325 burn patients were investigated from January to December 2019. All bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
3
1
Order By: Relevance
“…In our study, the proportion of Gram-negative bacteria was slightly higher than that of Gram-positive bacteria. This distribution was also consistent with that in other hospitals in Southwest China, 18 Iran, 19 and the United Kingdom. 20 According to CHINET reports, S. aureus was the most susceptible bacteria in burn patients in China, which was consistent with our results.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, the proportion of Gram-negative bacteria was slightly higher than that of Gram-positive bacteria. This distribution was also consistent with that in other hospitals in Southwest China, 18 Iran, 19 and the United Kingdom. 20 According to CHINET reports, S. aureus was the most susceptible bacteria in burn patients in China, which was consistent with our results.…”
Section: Discussionsupporting
confidence: 89%
“…While most of these studies investigated adults with/ without children, little information was available on pediatric burn patients. Despite the study participants being different from the formers (Rashid et al, 2019;Mater et al, 2020;Basit et al, 2021;Cato et al, 2021;Hashemzadeh et al, 2022), the primary pathogenic bacteria detected from the burn wound of pediatric patients were also S. aureus and P. aeruginosa in the present study. In other words, Staphylococcus and P. aeruginosa were the primary bacteria infected burn wounds that are irrelevant to the host's age.…”
Section: Discussioncontrasting
confidence: 61%
“…Studies have shown that S. aureus and P. aeruginosa were the leading bacteria isolated from burn wounds ( Rashid et al, 2019 ; Mater et al, 2020 ; Basit et al, 2021 ; Cato et al, 2021 ; Hashemzadeh et al, 2022 ). While most of these studies investigated adults with/without children, little information was available on pediatric burn patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, their antibiotic susceptibility profiles may differ from region to region, and even among different institutes and facilities, where compliance with infection control measures and antibiotic prescription practices also play important role. 7,8 In cases of burn infections, it is highly desirable that the antibiotics are used rationally and only according to the culture and sensitivity test reports. However, the culture and sensitivity / susceptibility test results take some time to become available to the clinicians.…”
Section: Introductionmentioning
confidence: 99%